2019
DOI: 10.1037/cpp0000296
|View full text |Cite
|
Sign up to set email alerts
|

Using the Child Behavior Checklist (CBCL) with transgender/gender nonconforming children and adolescents.

Abstract: Objective:The Child Behavior Checklist (CBCL) is a widely used instrument to screen for emotional and behavioral problems in children and adolescents. This study examined the impact that the choice of scoring template (male/female) had on scale scores in transgender and gender nonconforming (TGNC) youth as well as scores in the clinical range. Method: The analytic sample consisted of 108 participants (including 55 TGNC children ages 6 -11 years and 53 TGNC adolescents ages 12-18 years). Paired samples t tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…Finally, following Rider et al [25], this study examined differences in trans youth's mental health scores between evaluation by GID and ABAS norms. This paper showed that in the YSR-R, the mean scores in the main and problem scales differed significantly on four out of eleven scales among trans boys and on nine scales among trans girls between the binary gender norms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, following Rider et al [25], this study examined differences in trans youth's mental health scores between evaluation by GID and ABAS norms. This paper showed that in the YSR-R, the mean scores in the main and problem scales differed significantly on four out of eleven scales among trans boys and on nine scales among trans girls between the binary gender norms.…”
Section: Discussionmentioning
confidence: 99%
“…This process tends to be unclear when working with people who cannot identify with their ABAS. Most research groups used the ABAS for the evaluation [16][17][18], whereas some others mentioned uncertainty about which YSR/CBCL gender norm should be used with trans adolescents [14,16,25]. It is still unclear how to best use these instruments when working with trans and nonbinary people [25].…”
Section: Gender-related Distributions Of Psychological Distressmentioning
confidence: 99%
See 3 more Smart Citations